Global Healthcare Resource Efficiency in the Management of COVID-19 Death and Infection Prevalence Rates - Breitenbach, Marthinus C.; Ngobeni, Victor; Aye, Goodness C. (Frontiers in Public Health, 2021)
The scale of impact of the COVID-19 pandemic on society and the economy globally, provides a strong incentive to thoroughly analyse the efficiency of healthcare systems in dealing with the current pandemic and to obtain lessons to prepare healthcare systems to be better prepared for future pandemics. In the absence of a proven vaccine or cure, non-pharmaceutical interventions including social distancing, testing and contact tracing, isolation and wearing of masks are essential in the fight against the worldwide COVID-19 pandemic (Sarkar et al. 2020). We use Data Envelopment Analysis (DEA) and data compiled from Worldometers (2020), and The World Bank (2020a, 2020b & 2020c) to analyse how efficient the use of resources were to stabilise the rate of infections and minimise death rates in the top 36 countries that represented 90% of global infections and deaths out of 220 countries as of 11 November 2020. This is the first paper to model technical efficiency of countries in managing the COVID-19 pandemic by modelling death rates and infection rates as undesirable outputs using the approach developed by You & Yan (2011). We find that the average efficiency of global healthcare systems in managing the pandemic is very low, with only six efficient systems out of a total of 36 under the variable returns to scale assumption. This finding suggests that holding constant the size of their healthcare systems (because countries cannot alter the size of a healthcare system in the short run), most of the sample countries showed low levels of efficiency during this time of managing the pandemic; instead, it is suspected that most countries literally “threw” resources at fighting the pandemic, thereby probably raising inefficiency through wasted resource use.